The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4073/csr.2016.8
|View full text |Cite
|
Sign up to set email alerts
|

Community monitoring interventions to curb corruption and increase access and quality of service delivery in low‐ and middle‐income countries: a systematic review

Abstract: This Campbell systematic review assesses the effectiveness of community monitoring interventions in reducing corruption. The review summarises findings from 15 studies, of which seven are from Asia, six from Africa and two from Latin America. Community monitoring interventions can reduce corruption. They also improve use of health services, but no significant effect is found on school enrolments or dropouts. There is no improvement in health service waiting times, but there is an improvement in weight for age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 153 publications
2
31
0
Order By: Relevance
“…They recommend individual and collective expression of voice, or dedicated monitoring efforts as a means to claim rights. The implicit assumption is that increased citizen and policymaker knowledge, collective action and opportunities to dialogue with local providers and officials will lead to greater accountability regarding informal payments (George et al , 2005; Vian, 2008; Vian et al , 2012; Schatz, 2013; Pieterse and Lodge, 2015; Molina et al , 2016). There are some examples of local level health facility responsiveness, including regarding informal payments, stemming from community monitoring and other social accountability efforts (Dasgupta et al , 2015; Molina et al , 2016).…”
Section: Resultsmentioning
confidence: 99%
“…They recommend individual and collective expression of voice, or dedicated monitoring efforts as a means to claim rights. The implicit assumption is that increased citizen and policymaker knowledge, collective action and opportunities to dialogue with local providers and officials will lead to greater accountability regarding informal payments (George et al , 2005; Vian, 2008; Vian et al , 2012; Schatz, 2013; Pieterse and Lodge, 2015; Molina et al , 2016). There are some examples of local level health facility responsiveness, including regarding informal payments, stemming from community monitoring and other social accountability efforts (Dasgupta et al , 2015; Molina et al , 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has suggested that empowering local populations and promoting transparency on the performance of local leaders and service providers can improve public governance by increasing the demand for accountability. A recent systematic review by Molina et al (2016) finds that local monitoring can improve health services, though the evidence is limited due to a small number of studies. There is particularly little empirical evidence on the effectiveness of promoting social accountability in the context of largescale national programs (Devarajan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, accountability mechanisms extend beyond elections. One promising model is that of bottom-up monitoring , in which citizens receive information about the shortcomings of a given project so they can evaluate and pressure underperforming public officials (Kosack and Fung, 2014; Molina et al, 2016; Raffler et al, 2018). Proponents argue that bottom-up accountability is effective because: (a) constituents have first-hand information about the outcomes of local policies; (b) citizens have incentives to attack corruption that directly affects them; and (c) policy-makers are sensitive to social punishment from their own communities (Serra, 2011: 570).…”
Section: Introductionmentioning
confidence: 99%